Colorectal cancer among inflammatory bowel disease patients: risk factors and prevalence compared to the general population - Abu-Freha, Naim; Cohen, Bracha; Gordon, Michal; Weissmann, Sarah; Kestenbaum, Emily H.; Vosko, Sergei; Abu-Tailakh, Muhammad; Ben-Shoshan, Liza; Cohen, Daniel L.; Shirin, Haim (Frontiers in Medicine, 2023)
Background: Colorectal cancer (CRC) is a feared complication of inflammatory bowel disease (IBD). We aimed to investigate the prevalence and risk factors of CRC among a large cohort of IBD patients.Methods: Data on IBD patients free of CRC at baseline was extracted using the MDClone platform of the Clalit health maintenance organization in Israel. We investigated the frequency rate of CRC among IBD patients compared to a control group without IBD. Possible risk factors, including comorbidities and IBD-related medications, were investigated in a multivariate analysis.Results: During a follow-up of 139,448 years among Crohn's disease (CD) patients and 139,533 years among ulcerative colitis (UC) patients, a frequency rate of CRC was 1.5% (191) among 12,888 CD patients and 2.1% (261) among 12,381 UC patients–compared to 1.2% among 57,334 controls. In a multivariate analysis of UC patients, older age at diagnosis (OR 1.030, p<0.001), primary sclerosing cholangitis (OR 2.487, p=0.005), diabetes mellitus (OR 2.01, p<0.001), and glucocorticoids treatment (OR 1.465, p=0.008) were found to be predictors of CRC. For CD patients, older age at diagnosis (OR 1.035, p<0.001), primary sclerosing cholangitis (OR 2.25, p=0.029), and glucocorticoids treatment (OR 2.07, p<0.001) were found to be predictors for CRC, but not diabetes mellitus.Despite the continuously decreasing rates of CRC among IBD patients, these are still higher in IBD patients compared to the general population.IBD patients, particularly those with risk factors, require special consideration in follow-up for CRC.